Introduction to web accessibility : essential accessibility for everyone - Gay, Greg; Ryerson University; BC Open Textbook Project; BCcampus (Ryerson University, 2019)
"With raised awareness and accessibility laws emerging around the world, understanding what inclusive access to the Web means is becoming necessary knowledge for anyone who produces digital content. Much of the current information on Web accessibility requires some technical understanding, and may be difficult to consume for the average person. This book will "interpret" the W3C Web Content Accessibility Guidelines (WCAG 2.1), to make it easier to understand for a general audience. You will have an opportunity to experience barriers firsthand, then experience that content with the barriers removed, developing a practical understanding of web accessibility"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on September 18, 2019).
Keywords: Accessible Web sites for people with disabilities; Web sites -- Design; Electronic books